"For millions of people, this is real trauma": A pedagogy of political trauma in the wake of the 2016 U.S. Presidential election. (February 2018) - Sondel, Beth; Baggett, Hannah Carson; Dunn, Alyssa Hadley
Abstract: To explore how teachers navigated the days after the 2016 U.S. presidential election, we conducted a national, anonymous questionnaire. In this paper, we focus specifically on those participants who reported what we conceptualize as students' political trauma. Drawing on participants' responses, we outline a pedagogy to respond to this political trauma that includes: 1) attending to students' emotions; 2) emphasizing civic knowledge; and 3) developing students' critical consciousness and activism. We argue that these three domains collectively create opportunities to work toward the democratic and emancipatory purposes of education in the wake of politically traumatic events. Highlights: K-12 students showed evidence of political trauma following the 2016 U.S. Presidential election. In response, teachers tended to students' socio-emotional well-being. Teachers also worked to cultivate students' civic capacities. Teachers created opportunities for students to develop critical consciousness. These responses provide a pedagogical framework for teachers in times of political trauma.